1978
DOI: 10.3109/00365527809179804
|View full text |Cite
|
Sign up to set email alerts
|

Serum Gastric Inhibitory Polypeptide (GIP) in Duodenal Ulcer Disease: Relationship to Glucose Tolerance, Insulin, and Gastrin Release

Abstract: Serum immunoreactive gastric inhibitory polypeptide (IR-GIP), gastrin (IRG), and insulin (IRI) were estimated in 41 normal weight patients with duodenal ulcer (DU) and 25 age-matched controls in response to a high calorie liquid test meal. 28 out of 41 DU patients had a hyperglycaemic glucose response during the test meal, and 15 had a pathological oral glucose tolerance test. Fasting and food-stimulated IR-GIP and IRG levels were significantly elevated in the DU patients. Serum IRI also increased to significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…GIP appears to contribute to the regulation of pancreatic insulin release under physiological conditions; however, the precise contribution of this peptide to pathological states is unclear, as no definite and consistent abnormalities in GIP release in patients with diabetes mellitus have been found. Enhanced GIP release into the circulation has been reported in patients with obesity (43), chronic pancreatitis (44,45), and duodenal ulcer (46). In this last group of patients, increased fasting and foodstimulated serum GIP concentrations were found primarily in a subgroup ofpatients with an exaggerated early rise in serum glucose (46), further supporting its physiological role as a mediator of the enteroinsular axis.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…GIP appears to contribute to the regulation of pancreatic insulin release under physiological conditions; however, the precise contribution of this peptide to pathological states is unclear, as no definite and consistent abnormalities in GIP release in patients with diabetes mellitus have been found. Enhanced GIP release into the circulation has been reported in patients with obesity (43), chronic pancreatitis (44,45), and duodenal ulcer (46). In this last group of patients, increased fasting and foodstimulated serum GIP concentrations were found primarily in a subgroup ofpatients with an exaggerated early rise in serum glucose (46), further supporting its physiological role as a mediator of the enteroinsular axis.…”
Section: Resultsmentioning
confidence: 59%
“…Enhanced GIP release into the circulation has been reported in patients with obesity (43), chronic pancreatitis (44,45), and duodenal ulcer (46). In this last group of patients, increased fasting and foodstimulated serum GIP concentrations were found primarily in a subgroup ofpatients with an exaggerated early rise in serum glucose (46), further supporting its physiological role as a mediator of the enteroinsular axis.…”
Section: Resultsmentioning
confidence: 59%
“…In this study, we investigated the interrelationship between acid output and GIP release, and found that there was a positive correlation between maximum acid output in response to tetragastrin and integrated incremental response of GIP after oral glucose loading. As mentioned above, Arnold et al (1978) reported that both fasting and food-stimulated IR-GIP levels were significantly higher in duodenal ulcer patients. Moreover, in most patients with duodenal ulcer, the hyperacidity is related to vagus-dependency.…”
Section: Commentsmentioning
confidence: 72%
“…Through many investigations (Maxwell et al 1980; Yamagishi and Debas 1980; Simmons et al 1981), however, a lot of questions have been brought out as to the enterogastrone action of GIP. Arnold et al (1978) reported high levels of GIP both at fasting and after test meal loading in patients with peptic ulcer, and ruled out the hyposecretion of GIP as a cause of gastric acid hypersecretion in duodenal ulcer patients. Recently, it has become a popular belief that GIP is important for its insulinotropic effect (Anderson et al 1978).…”
mentioning
confidence: 96%
“…In our experiments we studied healthy volunteers only and the experimental conditions (diet, smoking, time of the test) were strictly controlled: in these conditions we never observed deterioration of glucose handling after oral glucose. It is possible, however, that cimetidine therapy in peptic ulcer patients could change the altered gut hormone profile [1] and then modify the insulin response to oral glucose.…”
Section: Discussionmentioning
confidence: 99%